Latitudinal clines in temperature and salinity tolerance in tidepool copepods - Leong, Wai (2020)
Local adaptation has been understudied in marine systems, but might be expected to be pronounced in the tidepool copepod Tigriopus californicus, which has a broad geographic range and extremely restricted dispersal. Tolerance to temperature and salinity was assessed in 14 populations over a 20° latitudinal range. Adaptive differentiation to temperature and salinity was found at scales as low as 5.6 km. Latitudinal clines were significant, with northern populations being more tolerant of low salinity and less tolerant of high temperature and high salinity. Both temperature and salinity tolerance were more closely associated with long-term thermal maxima than with long-term precipitation data. Hyperthermal and hyposmotic tolerance were inversely correlated, a pattern that could potentially slow adaptation to future conditions. Together, these studies of intraspecific geographic patterns in resistance to multiple stressors are important in predicting how environmental change may effect range shifts and local extinctions.